Amphibia, Anura, coastal zone, State of Piaui, northeastern Brazil. - Loebmann, Daniel; Giacometti Mai, Ana Cecilia (My University, 2008)
Amphibians are an important component of terrestrial and aquatic freshwater communities worldwide. Especially to the Northern coastal zone of Brazil, the knowledge about amphibian communities is very scarce. We have studied amphibian assemblages along the coastal strip zone of the state of Piaui for two years, covering a distance of ca. 70 km. It was possible to prepare a list of 21 anurans from 6 families (Microhylidae, Hylidae, Leptodactylidae, Cycloramphidae, Leiuperidae, and Bufonidae). All species are common and widely distributed in Brazilian territory, mainly on the Caatinga biome. The results are important to amplify the knowledge on the biodiversity found at the coastal zone of the state of Piaui.